UJI TOKSISITAS (Brine Shrimp Lethality Test) dan UJI AKTIVITAS ANTIBAKTERI DAUN KEMBANG BULAN (Tithonia diversifolia A. Gray) TERHADAP BAKTERI Staphylococcus aureus dan Escherichia coli - Mira Wahyuni; Chairul Saleh; Rudi Kartika (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2015)
Phytochemical, toxicity tests (Brine Shrimp Lethality Test) and the antibacterial activity of kembang bulan leaf (Tithonia diversifolia A. Gray). Phytochemical test results of secondary metabolites kembang bulan leaf (Tithonia diversifolia A. Gray) show that the ethanol extract contains alkaloids, flavonoids, steroids, phenolic and saponins. N-hexane fraction containing alkaloids and steroids. Ethyl acetate fraction contain flavonoids and steroids. Shrimp larvae toxicity test values obtained Lethal Concentration 50% (LC 50 ) at 383.5660 ppm ethanol extract, fractions 325.1583 ppm n-hexane and ethyl acetate fraction 196.3755 ppm. Test antibacterial activity against Staphylococcus aureus (Gram positive) and Escherichia coli (Gram negative) indicates that the most active fraction was ethanol extract the value of minimum inhibitory 1-2% (w / v) where the clear zone diameter of 8.5 to 9, 75 mm in the bacterium Escherichia coli and from 7.5 to 9.75 mm in Staphylococcus aureus.